Potential Mechanism and Perspectives of Mesenchymal Stem Cell Therapy for Ischemic Stroke: A Review - Zhu, Pengcheng; Tan, Hongtu; Gao, Haobo; Wang, Jiabin; Liu, Yangyang; Yang, Dongyi; Wu, Tao (Global Medical Genetics, 2024)
Mesenchymal stem cells (MSCs), as a stem cell type with multiple differentiation potentials and immune regulatory abilities, have shown broad prospects in the treatment of ischemic stroke in recent years. The main characteristics of MSCs include their self-renewal ability, differentiation potential for different types of cells, and the ability to secrete various bioactive factors such as cytokines, chemokines, and growth factors, which play a key role in tissue repair and regeneration. In the treatment of ischemic stroke, MSCs exert therapeutic effects through various mechanisms, including promoting vascular regeneration of damaged brain tissue, reducing inflammatory responses, and protecting neurons from damage caused by apoptosis. Research have shown that MSCs can promote the repair of ischemic areas by releasing neurotrophic factors and angiogenic factors, while inhibiting immune responses triggered by ischemia, thereby improving neurological function. With the in-depth study of its biological mechanism, MSCs have gradually shown good safety and effectiveness in clinical applications. Therefore, fully exploring and utilizing the potential of MSCs in the treatment of ischemic stroke may provide new ideas and solutions for future neural repair and regenerative medicine.
Keywords: mesenchymal stem cell; ischemic stroke; potential mechanism; self-renewal ability; chemokines